Rethinking district-level governance of malaria in Ghana: A narrative review - Nii Ayite Coleman (PLOS Global Public Health, 2022)
The goal of global malaria programming is to eliminate and eventually eradicate the disease. Achieving this global goal requires eliminating malaria in individual endemic countries. This paper, based on the observations of current and former implementers of malaria programs at district level, examines Ghana’s malaria strategy to determine its adequacy for the elimination of malaria in the country, with a focus on the governance of district health systems. The paper argues that Ghana’s malaria strategy is medically oriented, focusing predominantly on diagnosis and treatment of the disease. The strategy ignores determinants of malaria that are related to lifestyle and environment. Furthermore, there is limited engagement with other district-level stakeholders, and what engagement does occur is neither systematic nor sustained. Ghana’s malaria strategy therefore requires a systematic rethinking to mobilize the participation of communities in district governance for malaria. The paper proposes several possible actions to restructure district governance of malaria. In Ghana, the malaria program should engage with key stakeholders in districts, using a systematic and sustained approach, to strengthen multisectoral action and community participation. This will require new accountability relationships for malaria progress within communities and among District Assemblies, district health authorities, and communities. Malaria programs in other African countries may also need to be similarly redirected towards community health governance for malaria progress. Simultaneously, global health and malaria agencies should redefine malaria as a social problem and collectively adopt a social determinants approach to strengthening national malaria programs. Pursuing the goals of elimination and eventual eradication of malaria without incorporating effective control of mosquito breeding and public health regulation is a fundamentally flawed approach. Progress on malaria requires a paradigm shift, from a medical perspective to a social determinant-informed approach with sustained and systematic engagement of all stakeholders in local communities.